The Relationship between Knowledge and Anxiety Levels in Preoperative Cataract Surgery Patients at the Eye Clinic, Dr. Rom. Djoelham Binjai 2022 - Nanarita Tarigan (Institute of Computer Science (IOCS), 2022)
Cataract is a condition of decreased vision due to clouding of the eye lens. If the lens becomes cloudy, then vision also becomes blurred. Cataracts are generally a disease in the elderly around the age of 50 years, or also called art cataracts. Objectives To determine the relationship between knowledge and anxiety levels in preoperative cataract surgery patients at the Eye Polyclinic, RSUD Dr. RM. Djoelham Binjai in 2022. The factors that cause cataracts are age, physical, chemical, predisposing diseases, genetics, and viral infections during fetal growth. There are various factors that cause cataracts, including: The results showed that out of 30 respondents, the majority of patients were anxious about pre-cataract surgery, amounting to 18 people and a minority of patients not being anxious about pre-cataract surgery, amounting to 12 people.Based on the results of the chi square test, the relationship between knowledge and anxiety levels in preoperative cataract surgery patients at the Eye Polyclinic of RSUD Dr. RM. Djoelham Binjai in 2022 with a degree of significance (α) = 0.05 and df = 1, the calculation results are Sig (2-tailed) 0.025 < (α) = 0.05, then Ho is rejected and Ha is accepted